AFFIXATION IN THE UTTERANCE OF MANDURO SOCIETY - Kristanti, Ika Lusi; Mayasari, Diana; Ahya, Akhmad Sauqi (JEELL (Journal of English Education, Linguistics and Literature), 2017)
Language as a means of daily communication, will get shift and extinction if the native speakers no longer use the language. The factors that influence are the factors of social, economic, political, cultural and bilingual or even the multilingual that the speaker has. This phenomenon occurs in the utterance of Manduro society. Thus, it needs an effort to preserve the language so that language extinction does not occur in that language. One method that can be used is to socialize the language to the public so that native speakers can freely use the language wherever located. This phenomenon encourages researchers to conduct research in the affixation of Manduro society’s utterance as an effort to preserve language in the utterance of Manduro society  in order to avoid language extinction. The type of this research is descriptive qualitative. The sample is chosen by using purposive sampling technique. Data collection techniques used are interview, recording, observation, and Swadesh Morris questionnaire to obtain the vocabulary. Data analysis technique used is inductive analysis with data classification by using the methods of padan and agih, reduction, limiting the scope of theory, and drawing conclusion. Based on the result that has been achieved by the researchers, there is affixation process in the utterance of manduro society, such as: prefix, suffix, and confix. The affixation process is influenced by Javenese languange and Indonesian language.